The Plastid Casein Kinase 2 Phosphorylates Rubisco Activase at the Thr-78 Site but Is Not Essential for Regulation of Rubisco Activation State - Kim, Sang Y.; Bender, Kyle W.; Walker, Berkley J.; Zielinski, Raymond E.; Spalding, Martin H.; Ort, Donald R.; Huber, Steven C. (Frontiers in Plant Science, 2016)
Rubisco activase (RCA) is essential for the activation of Rubisco, the carboxylating enzyme of photosynthesis. In Arabidopsis, RCA is composed of a large RCAα and small RCAβ isoform that are formed by alternative splicing of a single gene (At2g39730). The activity of Rubisco is controlled in response to changes in irradiance by regulation of RCA activity, which is known to involve a redox-sensitive disulfide bond located in the carboxy-terminal extension of the RCAα subunit. Additionally, phosphorylation of RCA threonine-78 (Thr-78) has been reported to occur in the dark suggesting that phosphorylation may also be associated with dark-inactivation of RCA and deactivation of Rubisco. In the present study, we developed site-specific antibodies to monitor phosphorylation of RCA at the Thr-78 site and used non-reducing SDS-PAGE to monitor the redox status of the RCAα subunit. By immunoblotting, phosphorylation of both RCA isoforms occurred at low light and in the dark and feeding peroxide or DTT to leaf segments indicated that redox status of the chloroplast stroma was a critical factor controlling RCA phosphorylation. Use of a knockout mutant identified the plastid-targeted casein kinase 2 (cpCK2α) as the major protein kinase involved in RCA phosphorylation. Studies with recombinant cpCK2α and synthetic peptide substrates identified acidic residues at the -1, +2 and +3 positions surrounding Thr-78 as strong positive recognition elements. The cpck2 knockout mutant had strongly reduced phosphorylation at the Thr-78 site but was similar to wild type plants in terms of induction kinetics of photosynthesis following transfer from darkness or low light to high light, suggesting that if phosphorylation of RCA Thr-78 plays a direct role it would be redundant to redox regulation for control of Rubisco activation state under normal conditions.